Money and Information - Berentsen, Aleksander; Rocheteau, Guillaume (Review of Economic Studies, 2004)
This paper investigates the role of money in markets in which producers have private information about the quality of the goods they supply. When the fraction of high-quality producers in the economy is given, money promotes the production of high-quality goods, which improves the quality mix and welfare unambiguously. When this fraction is endogenous, however, we find that money can decrease welfare relative to the barter equilibrium. The origin of this inefficiency is that money provides consumption insurance to low-quality producers, which can result in a higher fraction of low-quality producers in the monetary equilibrium. Finally, we find that most often agents acquire more costly information in the monetary equilibrium than in the barter equilibrium. Consequently, money is welfare-enhancing because it promotes useful production and exchange, but not because it saves information costs. Copyright 2004, Wiley-Blackwell.